2001
DOI: 10.21273/hortsci.36.4.732
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatments Control Extension Growth and Enhance Microbial Disinfection of Minimally Processed Green Onions

Abstract: Extension growth of minimally processed (removal of roots and compressed stem) green onions (Allium cepa L. × A. fistulosum L.) was greatly reduced by storage in air at 0 °C, while growth of 10-20 mm occurred at 5 °C over 10 days. Heat treatments of 52.5 and 55 -°C water for 4 and 2 min, respectively, were especially effective in reducing growth to less than 5 mm during 12-14 days at 5 °C. Growth was inhibited irrespective of whether the heat treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 15 publications
1
25
0
2
Order By: Relevance
“…Color values ( a *, b *, and L *) were significantly different on day 9 and 12, though the increase was small (Figure 5). The results showed that discoloration of fresh‐cut green onions resulted in decreased a * and increased b * and chroma color values; but the changes in L * and hue values were not consistent (Cantwell and others 2001). Although the results showed that treated samples were statistically significantly different from controls, the hue angle (°) of all mint samples remained at about 179° regardless of irradiation doses (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Color values ( a *, b *, and L *) were significantly different on day 9 and 12, though the increase was small (Figure 5). The results showed that discoloration of fresh‐cut green onions resulted in decreased a * and increased b * and chroma color values; but the changes in L * and hue values were not consistent (Cantwell and others 2001). Although the results showed that treated samples were statistically significantly different from controls, the hue angle (°) of all mint samples remained at about 179° regardless of irradiation doses (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Negative a * indicates green and higher positive b * indicates more yellow color. The chroma ( C ) value indicates color intensity or saturation, calculated as C = ( a * 2 + b * 2 ) 1/2 (Cantwell and others 2001). Hue angle was calculated as H°= 180°+ tan −1 ( b */ a *) when a * < 0 and H°= tan −1 ( b */ a *) when a *> 0 and b *≤ 0 (Fukumoto and others 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many fruits and vegetables tolerate water temperatures of 50 to 60 °C for up to 10 min, but shorter exposure at these temperatures may also control many postharvest plant pathogens (Barkai‐Golan and Phillips 1991). Immersion of fresh fruits and vegetables in hot water has been used to reduce physiological disorders, control surface microorganisms and decay, eradicate insects, or maintain quality in a variety of fresh commodities such as fresh‐cut green onions (Cantwell and others 2001; Kim and others 2005), strawberries (Wszelaki and Mitcham 2003; Karabulut and others 2004), avocados (Woolf and Laing 1996), broccoli (Forney 1995), mango (Sharp and others 1989), and sweet pepper (Fallik and others 1999). Up to now, there was limited knowledge of the effects of applying hot water treatments on decay control, microbial quality, and volatile biosynthesis of blueberries ( Vaccinium corymbosum L.).…”
Section: Introductionmentioning
confidence: 99%
“…Yellowing of the stems (Kasim, 2009) and/or loss of green pigmentation of the leaves (Cantwell, Suslow, & Hong, 2001) after treatment or during shelf-life are considered color defects of green onions. Thus, the b values (yellowness) of green onion stems and a values (greenness) of leaf have been investigated in our study.…”
Section: Survival Population Of Salmonella On Green Onions During Stomentioning
confidence: 99%